Flexible Metal Forming Technologies Principles, Process and Equipment - Guo, Xunzhong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book systematically introduces the principles of flexible forming technologies to manufacture thin-walled complex-shaped components, the mechanism of controlling the material flow, the design and the configuration of flexible forming technologies$1 (Bequipment and tools. It covers new technologies and new processes for forming hollow components, and relevant research on forming mechanisms, deformation laws, and defect control with examples from practical applications. It will be a useful reference for researchers, engineers, graduate and undergraduate students in aerospace, nuclear, railway, vehicle and petrochemical engineering, etc.s
Introduction and State of the Art of Flexible Forming Technologies -- Flexible Incremental Sheet Metal Forming Technology -- Flexible Spinning Sheet Metal Forming Technology -- Flexible Multi-point Sheet Metal Forming Technology -- Flexible 3D Profile Roll Forming Technology -- Profile 3D Quench Forming Technology -- Tube 3D Free Bending Technology -- Flexible Tube Rolling Bending -- Flexible Tube Die-less Forming.
Keywords: Manufactures; Engineering design; Industrial engineering; Production engineering; Materials; Metals; Building materials; Machines, Tools, Processes; Engineering Design; Industrial and Production Engineering; Materials Engineering; Steel, Light Metal; Metals -- Formability; Metal-work